The Meat of the Matter: The Effect of Science-based Information on Consumer Perception of Grass-fed Beef - Klae D O'Brien; Carrie N Baker; Sarah A. Bush; Kattlyn J Wolf (Journal of Applied Communications, 2023)
In the United States, there is a growing disconnect between consumers and their food source, leading to a lack of knowledge and trust in the agricultural food system. Urbanization has moved people away from farms, ranches, and food production; and the information consumers seek about their food is filtered through mass and social media. Portrayals of information about food production, specifically beef, from outside the agriculture industry often present polarizing and conflicting information about beef production and its implications for the health and well-being of humans, livestock, and the environment. This adds to consumer confusion and influences purchasing behaviors. Using a quasi-experimental pretest-posttest 2x2 factorial design, we sought to explore consumer (n = 60) perceptions, consumption, and purchasing behaviors of grass-fed beef and determine the effects of four information treatments on overall perception. Descriptive results showed consumers do not have a shared definition pertaining to grass- and grain-fed beef, citing the internet as their most referenced source for information about food and grass-fed beef. Results from a t-test indicated that exposing consumers to an information treatment had a significant effect on environmental impacts, cost, quality/nutrition, and overall perception of grass-fed beef. A between-subjects factorial ANOVA revealed there was no significant difference in perception based on treatment type. Efforts to raise awareness about beef production, on-farm practices, and links between food and grower could be warranted to help enhance the trust and credibility of the industry and bridge the gap between producers and consumers.
Keywords: Consumer perceptions; beef production; trustworthiness